The contribution of yogurt to nutrient intakes across the life course. Issue 1 (March 2015) - Williams, E. B.; Hooper, B.; Spiro, A.; Stanner, S.
Abstract Yogurt is a nutrient‐dense food within the milk and dairy products food group. The nutritional content of yogurt varies depending on the processing method and ingredients used. Like milk, it is a good source of protein and calcium, and can be a source of iodine, potassium, phosphorus and the B vitamins – riboflavin (B2) and vitamin B12 (depending on type). Some yogurt products are also fortified with vitamin D. The nutritional value of dairy products (milk, cheese and yogurt) and the importance of the nutrients they provide for bone health are well recognised. These foods are collected together as one of the four main food groups within the UK's eatwell plate model that illustrates a healthy, balanced diet. Studies exploring the nutritional and health attributes of yogurt are limited but some research has suggested benefits in relation to bone mineral content, weight management, type 2 diabetes and metabolic profile. Yogurt consumption has also been associated with diet quality. The aim of this paper is to use national survey data to examine yogurt consumption in the UK and consider its contribution to nutrient intakes at different life stages within the context of nutritional challenges in each age group. The contribution of yogurt to energy and nutrient intakes across the life course was calculated via secondary analysis of data from the Diet and Nutrition Survey of Infants and Young Children (2011) and the National Diet and Nutrition Survey (2008/2009–2010/2011). The products categorised within the 'yogurt group' included all yogurt, fromage frais and dairy desserts, and fortified products. Comparisons were also made between specific sub‐categories of yogurt, namely 'yogurt', 'fromage frais' and 'dairy desserts'. Nutrients included in the analyses were energy; the macronutrients; micronutrients that yogurt can be defined as a 'source of'; micronutrients that may be of concern in the UK population; and vitamin D for fortified products. A simple dietary modelling exercise was also undertaken to investigate the potential impact of including an additional pot of yogurt per day on the nutrient intakes of adolescents. Children aged 3 years and under had the highest intakes of yogurt [mean intake 43.8 g/day (SD 39.7 g) in 4–18 month‐olds; 46.7 g/day (SD 39.1 g) in 1.5–3 year‐olds], and adolescents (11–18 years) consumed the least [21 g/day (SD 38.0 g)]. In adults, highest mean consumption [35.7 g/day (SD 55.0 g)] was during middle age (50–64 years), equivalent to less than a third of a standard 125 g pot. Around 80% of young children (aged 3 years and under) but only a third of teenagers and young adults had consumed any yogurt product during the survey period of 4 days. Average yogurt consumption was twice as high in women as men among older adults (65 years and over), while gender differences in consumption were less apparent in children. Fromage frais and fortified yogurt products were most commonly consumed by younger children, as were dairy desserts in those aged 4–18 years. Among adults, yogurt per se was most commonly consumed. Children aged 4–10 years exhibited the most variety in the types of yogurt consumed. Low‐fat yogurt (including those with added fruit, nuts and cereals) was the most commonly consumed yogurt type when all ages were combined. More than a third of all yogurt products consumed by children aged 3 years and under were fortified, compared with 18% in those aged 4–10 years. During adulthood, the consumption of fortified products was negligible. The yogurt group made a useful contribution to micronutrient intakes in children aged 4 months to 10 years, particularly vitamin B12 (4–18 months: 7.6%; 1.5–3 years: 5.3%; 4–10 years: 3.8%), riboflavin (7.8%, 6.9%, and 5.7%, respectively), calcium (9.5%, 8.2%, and 5.9%, respectively), iodine (7.2%, 7.6%, and 7%, respectively) and phosphorus (8.1%, 6.3%, and 4.3%, respectively). It also provided 3.9% of the total intake of vitamin D in those aged 4–18 months and 10.5% in those aged 1.5–3 years. Although the contribution to total dietary energy intake was low (4.9% at 4–18 months and 4.2% at 1.5–3 years), yogurt contributed a high proportion of non‐milk extrinsic sugars (NMES) to the diets of young children (22.7% and 11.1% in 4–18 months and 1.5–3 years, respectively). However, the total NMES intake was comparatively low in children aged 4–18 months (6.7% total energy), and 11.6% in 1.5–3 year‐olds (compared to 15.3% total energy in children aged 11–18 years in this survey). As children aged, the contribution of yogurt (all categories combined) to micronutrient intake, as well as to NMES, decreased, reflecting the increasing amounts and variety of foods in the diet. Yogurt made a small contribution to energy and macronutrient intakes during adulthood, with the greatest proportions mostly in the older age group (65 years and over) (energy: 1.7%; fat: 1.3%; saturated fatty acids: 2.1%; NMES: 4%). As intake was higher among women, yogurt made a greater contribution to their micronutrient intakes compared with men, providing >5% of the reference nutrient intakes (RNIs) for phosphorus, iodine, calcium, vitamin B12 and riboflavin. Simple dietary modelling was carried out to investigate the hypothetical change in mean nutrient intakes among adolescents aged 11–14 and 15–18 years, if they were all to add an extra 125 g pot of low‐fat fruit yogurt to their current diet. This showed an increase in average intake, as a percentage of the RNI, for several micronutrients for which there is some evidence of low intakes in this age group, notably calcium in boys and girls (11–18 years) and iodine in girls (11–18 years). Although some benefits for micronutrient intakes were noted, such advice would impact on energy and macronutrient intakes (including NMES), and would need to be given in the context of the wider diet (e.g. as 'swaps' for less nutrient‐dense foods). In conclusion, yogurt makes a small but valuable contribution to nutrient intakes in the UK, particularly in young children. Among adolescents, the addition of a low‐fat yogurt would help meet recommended intakes for several micronutrients, particularly calcium and iodine, which are of concern in some teenage diets. Advice to replace some types of snacks and desserts, particularly those high in fat and sugars and low in micronutrients, with a pot of yogurt or similar dairy product may improve the nutrient density of their diet.